2022
DOI: 10.3389/fnmol.2022.888318
|View full text |Cite
|
Sign up to set email alerts
|

First Metabolomic Signature of Blood-Brain Barrier Opening Induced by Microbubble-Assisted Ultrasound

Abstract: Microbubble (MB)-assisted ultrasound (US) is a promising physical method to increase non-invasively, transiently, and precisely the permeability of the blood-brain barrier (BBB) to therapeutic molecules. Previous preclinical studies established the innocuity of this procedure using complementary analytical strategies including transcriptomics, histology, brain imaging, and behavioral tests. This cross-sectional study using rats aimed to investigate the metabolic processes following acoustically-mediated BBB op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The ultrasound parameters used were chosen given their effectiveness in delivering therapeutic molecules in various contexts. For example, these parameters have been used to increase the permeability of the blood-brain barrier [ 45 ] or to increase the extravasation of local drug delivery to tumor tissue [ 48 ], as well as in previous studies regarding sonoporation of the RWM [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Some previous studies demonstrated increased steroid delivery to the inner ear using 1-MHz ultrasound waves [ 28 ] and increased safety (according to histology) with 3 rather than 5 one-minute consecutive exposures for the RWM [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasound parameters used were chosen given their effectiveness in delivering therapeutic molecules in various contexts. For example, these parameters have been used to increase the permeability of the blood-brain barrier [ 45 ] or to increase the extravasation of local drug delivery to tumor tissue [ 48 ], as well as in previous studies regarding sonoporation of the RWM [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Some previous studies demonstrated increased steroid delivery to the inner ear using 1-MHz ultrasound waves [ 28 ] and increased safety (according to histology) with 3 rather than 5 one-minute consecutive exposures for the RWM [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 45 ], Vevo MicroMarker ® MBs (VisualSonics—Fujifilm, Amsterdam, the Netherlands) are composed of a mixture of nitrogen and perfluorobutane gases encapsulated in a thin and flexible monolayer of phospholipids. MBs were prepared according to the manufacturer’s instructions (with 1 min of hand stirring and 10 min of resting at room temperature) and then diluted 10 times to reach a concentration of 2 × 10 8 MB/mL.…”
Section: Methodsmentioning
confidence: 99%
“…3b ). Another effort to non-invasively deliver drugs across the BBB is the use of intravascular microbubbles combined with focused ultrasound which disrupts the vasculature [ 141 , 142 ] ( Fig. 3c ), which could potentially be applied to EV administration.…”
Section: Administration Routes For Evs To Deliver Cargo To the Brainmentioning
confidence: 99%
“…(b) Intravascular microbubbles combined with focused ultrasound could potentially be applied to delivery of EVs into the CNS [ 140 ]. (c) EVs from various sources, including plants, milk and bacteria conjugated with microRNA molecules and administered orally were detected in mouse brain [ 141 , 142 ]. (d) Intravenous injection of EVs has the potential to deliver EVs to the brain but is limited due to limited biodistribution time and high clearance in peripheral organs [ 143 ] (e) Intraperitoneal injection showed high cell uptake of EVs at the local injection site [ 143 ] (f) Subcutaneous injection resulted in the lowest uptake of EVs by brain cells [ 129 ].…”
Section: Figmentioning
confidence: 99%